Influence of infused water cucumber to decrease blood pressure in elderly Hypertension: A Literature Review - Fauziah, Wardah; Kurniawan, Wawan; Wahyudin, Teguh (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2020)
The Elderly is a person over 60 years of age who is heavily at risk of Hypertesnia disease. Hypertension is an uncontagious disease, which has increased prevalence in Indonesia from 2013 to 2018. The purpose of this writing is to determine the influence of infused water cucumber on the decline in blood pressure in the elderly and to study the benefits of infused water cucumber. The search method of the library resource is done online using databases such as Google Scholar. The keywords used are